Adopting a no-fault compensation scheme for motor vehicle accidents in Malaysia: a myth or reality - Amin, Naemah; Nicholson, Charles (2013)
The present tort compensation scheme which has been widely adopted in common law jurisdictions to address the financial needs of injured victims has been found to be riddled with deficiencies. In focusing on negligence and causation as the foundation of liability, the adversarial system of the law has been strongly criticized as, failing to provide fitting and timely compensation, requiring injured claimants to go through difficult, stressful and long, drawn out litigation procedures coupled with significant legal fees and administrative costs. Concern over tort’s effectiveness as an appropriate personal injury compensation mechanism for victims of motor vehicle accidents and the realization that the traditional tort system developed in the days of the horse and carriage was never contemplated to address contemporary issues facing accident victims, a number of common law jurisdictions have initiated significant departures from the system and have moved in the direction of adopting an alternative no-fault compensatory model where all persons injured in road accidents obtain compensation regardless of establishing fault thus shifting the focus on the needs of the injured victim rather than on one’s culpability. These modern compensation schemes are premised on the philosophy of community responsibility, social justice and public benefit. This paper surveys the failings of current system of civil liability in the tort of negligence for motor vehicle accidents and undertakes a comparative analysis to evaluate the arguments in support of the introduction of such a scheme in Malaysia, its viability and challenges.